Analysis of Solubility, pH, Antimicrobial Action and Cytotoxicity of Calcium Hydroxide Paste Associated With Ambroxol Hydrochloride - Mota, Thaís Ferreira Rodrigues; Cassiano, Ana Flávia Balestrero [UNESP]; Titato, Pedro César Gomes; Calefi, Pedro Henrique Souza; Alcalde, Murilo Priori; Faria, Gisele [UNESP]; Duarte, Marco Antonio Hungaro (Wiley, 2025)
This study evaluated the association of ambroxol hydrochloride with calcium hydroxide paste as intracanal medication to enhance antimicrobial action on biofilm without affecting pH, solubility and cytotoxicity. Calcium hydroxide (CH) paste and formulations with different ambroxol concentrations were placed into artificial teeth conditioned in distilled water. pH and solubility were measured. Dentine discs infected with E. faecalis were covered with pastes, and biofilm viability was analysed using live/dead assay and confocal microscope. Cytotoxicity was analysed using MTT assay on fibroblast and osteoblast-like cells. Data were statistically compared (p < 0.05). Ambroxol showed an acidic pH after 7 days, compared to CH, but the 30% concentration became more alkaline after 30 days. While CH's pH decreased over time, ambroxol groups maintained stability. Solubility decreased for all groups over time. All groups showed significant antimicrobial differences from the control group. The association did not alter CH's cytotoxicity. Further research is needed for optimal ambroxol concentration.